Pendampingan Guru PAUD dalam Pembelajaran Berkebun Edukatif Berbasis Pertanian Ramah Anak: Pengabdian - Harini Suci; Ade Yoga Rohmandani (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
This Community Service (PKM) activity aims to improve the competence of Early Childhood Education (PAUD) teachers in designing and implementing educational gardening learning based on child-friendly agriculture as an effort to stimulate the development and formation of environmentally conscious character in early childhood. PKM was implemented at Trate Mas Maospati Kindergarten, with PAUD teachers as the primary target, while early childhood children became indirect beneficiaries. The implementation method included preparation, socialization, mentoring, learning practice, as well as reflection and evaluation. Socialization focused on introducing the concept of child-friendly agriculture and the benefits of gardening activities for early childhood development. Mentoring was carried out through guidance in preparing lesson plans and direct practice of simple gardening activities that are safe and appropriate to the characteristics of children. The results of the activity showed an increase in the understanding and skills of PAUD teachers in integrating gardening activities into daily learning. Teachers were able to design more contextual learning activities based on direct experience. In addition, children demonstrated active involvement in planting, caring for, and observing plants, which had a positive impact on motor and cognitive stimulation, as well as environmental awareness.